1996
DOI: 10.1557/proc-452-977
|View full text |Cite
|
Sign up to set email alerts
|

Purely Intrinsic Poly-Silicon Films by Hot Wire Chemical Vapor Deposition

Abstract: Poly-silicon films have been prepared by hot-wire chemical vapor deposition (HWCVD) from hydrogen diluted silane gas at a low temperature (430 °C). The optical gap of the poly-silicon films is 1.1 eV, though with a higher optical absorption than c-Si. The grains have a preferential orientation (220) perpendicular to the substrate with an average crystallite size of 70 nm. The crystalline volume fraction is 95% with complete coalescence of grains. Large structures up to 0.5 μm could be observed in the AFM micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Whereas the material made at high hydrogen dilution is completely crystalline with no noticeable amorphous incubation phase, it is very defective and porous, characterised by the typical 2100 cm −1 mode of vibration in the IR spectrum and this material goes through fast post deposition oxidation (becomes n-type). On the other hand, the films made at low hydrogen dilution have the characteristics of a compact structure, and hydrogen atoms in the film are at compact sites [24] (2000 cm −1 in IR spectrum [25]). These sorts of materials showed the device quality, but suffered from amorphous incubation phase, being in a deposition regime near to the amorphous transition regime [26].…”
Section: Transition Type Materialsmentioning
confidence: 99%
“…Whereas the material made at high hydrogen dilution is completely crystalline with no noticeable amorphous incubation phase, it is very defective and porous, characterised by the typical 2100 cm −1 mode of vibration in the IR spectrum and this material goes through fast post deposition oxidation (becomes n-type). On the other hand, the films made at low hydrogen dilution have the characteristics of a compact structure, and hydrogen atoms in the film are at compact sites [24] (2000 cm −1 in IR spectrum [25]). These sorts of materials showed the device quality, but suffered from amorphous incubation phase, being in a deposition regime near to the amorphous transition regime [26].…”
Section: Transition Type Materialsmentioning
confidence: 99%
“…Note that this situation which applies to intrinsic µc-Si:H is in contrast to the situation prevailing for the very thin doped µc-Si:H layers which are used as contact layers in amorphous and other thin-film silicon solar cells [8]. When using hot-wire CVD, very high deposition rates up to 50 Å/s for silicon (µc-Si:H / poly-Si) have been reported [9]; this fact illustrates that high deposition rates should not be excluded a priori for µc-Si:H. Indeed, encouraging first results on cells showed 3 % conversion efficiency for the hot wire technique at a deposition rate of 5 Å/s [10]. Within the field of plasma-enhanced CVD (PECVD), it has been shown that the VHF-GD technique, where the plasma excitation frequency is increased to the VHF-range, is very favourable for the growth of µc-Si:H [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…21) We measured the generation lifetime of the MOS capcitor and used it as an indicator to estimate the crystallinity and impurities level in the grain boundary. Since the conductivity of poly-Si is lower than single crystal silicon, [22][23][24] we detected more sensitively the behavior of carriers generated from impurities in deep depletion state. Also, the high roughness of poly-Si reacted at the physical deep position of SiO 2 and generated slow state traps (border traps).…”
Section: Introductionmentioning
confidence: 99%